Conditional probability of long-term survival after resection of hilar cholangiocarcinoma. Issue 6 (June 2016) - Buettner, Stefan; Margonis, Georgios A.; Kim, Yuhree; Gani, Faiz; Ethun, Cecilia G.; Poultsides, George; Tran, Thuy; Idrees, Kamran; Isom, Chelsea A.; Fields, Ryan C.; Krasnick, Bradley; Weber, Sharon M.; et al.
Abstract: Background: While traditional survival analyses focus on factors determined at the time of surgery, conditional survival (CS) estimates prognosis relative to time following treatment. We sought to compare actuarial and CS among patients undergoing curative intent surgery for hilar cholangiocarcinoma. Methods: 242 patients undergoing surgery between 2000 and 2014 were identified using a multi-institutional database. CS was calculated as the probability of surviving an additional 3 years, given that the patient had already survived "x" years from surgery. Results: Median patient age was 67 years (IQR: 57–73) and most patients were male (n = 140, 57.9%). Lymph node metastases were noted in 79 (32.6%) patients while an R0 margin was obtained in 66.1% (n = 160). Median OS was 22.3 months. Actuarial survival decreased over time from 46.3% at 2 years following surgery to 18.2% at 5 years; in contrast, the 3-year CS (CS3 ) increased with time (CS3 at 2 years was 39.3% versus 54.4% at 5 years). CS3 exceeded actuarial survival for high-risk patients with patients with perineural invasion demonstrating an actuarial survival of 15.4% at 5 years versus CS3 of 37.6% at 2 years following surgery (Δ = 22.2%). Conclusions: CS provides a more accurate, dynamic estimate for survival, especially among high-risk patients.